Tackling regional skill shortages: From single employer strategies to local partnerships - Suleman, F.; Videira, P.; Araújo, E. R. (Journal of Vocational Education and Training, 2023)
This research examines regional skill problems and the strategies adopted to reduce skill shortages by a set of employers (n = 16). The data collected in 2019 in a northern region in Portugal indicate considerable and persistent shortages of engineering and IT graduates and non-graduates for operational jobs. The employers implement anticipative strategies interacting with the education system, and the city council has developed a multi-stakeholder partnership. However, the most widespread strategy is remedial and consists of employer-provided training. Employers believe that the partnership has been a fruitful way of expanding economic activities, but further efforts are required to alleviate skill shortages.